“LANGUAGE INTERFERENCE AND METHODS OF ITS OVERCOMING INFOREIGN LANGUAGE TEACHING” (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Innovative research in modern education has been focused on exploring and implementing new approaches to teaching and learning that are more effective, engaging, and personalized for students. This research has led to the development of various innovative technologies and methodologies, such as gamification, adaptive learning, and virtual reality, that have revolutionized the way students learn and teachers teach. This abstract will discuss some of the key findings and trends in innovative research in modern education, including the benefits of personalized learning, the importance of teacher training and support, and the potential of technology to transform education. It will also highlight some of the challenges and limitations of these new approaches and suggest areas for future research and development.